Selective inhibition of monoamine oxidase A by hispidol. Issue 4 (15th February 2018) - Baek, Seung Cheol; Lee, Hyun Woo; Ryu, Hyung Won; Kang, Myung-Gyun; Park, Daeui; Kim, Soo Hyun; Cho, Myoung-Lae; Oh, Sei-Ryang; Kim, Hoon
Graphical abstract: Highlights: Hispidol was a potent (IC50 = 0.26 µM) and selective inhibitor for human MAO-A. Hispidol was a reversible and competitive inhibitor (Ki = 0.10 µM). The binding affinity of hispidol for MAO-A was greater than that for MAO-B. Addition of 3′-hydroxyl group to hispidol might reduce the inhibitory activities against MAO enzymes. Hispidol can be considered a novel lead compound for development of novel MAO inhibitors. Abstract: Hispidol, an aurone, isolated from Glycine max Merrill, was found to potently and selectively inhibit an isoform of recombinant human monoamine oxidase-A (MAO-A), with an IC50 value of 0.26 µM, and to inhibit MAO-B, but with lower potency (IC50 = 2.45 µM). Hispidol reversibly and competitively inhibited MAO-A with a Ki value of 0.10 µM with a potency much greater than toloxatone (IC50 = 1.10 µM), a marketed drug. It also reversibly and competitively inhibited MAO-B (Ki = 0.51 µM). Sulfuretin, an analog of hispidol, effectively inhibited MAO-A (IC50 = 4.16 µM) but not MAO-B (IC50 > 80 µM). A comparison of their chemical structures showed that the 3′-hydroxyl group of sulfuretin might reduce its inhibitory activities against MAO-A and MAO-B. Flexible docking simulation revealed that the binding affinity of hispidol for MAO-A (−9.1 kcal/mol) was greater than its affinity for MAO-B (−8.7 kcal/mol). The docking simulation showed hispidol binds to the major pocket of MAO-A or MAO-B. The findings suggest hispidol is a potent, selective, reversible inhibitor of MAO-A, and that it be considered a novel lead compound for development of novel reversible inhibitors of MAO-A.